Mining policy in post-conferderation Newfoundland with Hon. J. R. Smallwood - Canadian Institute of Mining and Metallurgy. Avalon Branch. (Memorial University of Newfoundland. Division of Educational Technology, 1979)
ETV Moble production. J. R. Smallwood addresses the Avalon Chapter of The Canadian Institute of Mining and Metallurgy.